Manajemen Bandwidth Jaringan dengan Metode Per Connection Queue (PCQ) Pada Mikrotik di Masterpiece Family Karaoke Tebet - Anwar, Imam Dzikrilloh; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Masterpiece Family Karaoke Tebet frequently faces bandwidth management issues, especially during evenings and weekends due to uneven bandwidth usage. This causes network congestion and a decline in service quality, negatively impacting customer experience. To address this issue, this study applies the Per Connection Queue (PCQ) method on MikroTik devices. The PCQ method ensures fair and efficient bandwidth distribution among users and manages usage time to maintain network stability. This study involves several stages: problem identification, a literature review to explore previously applied bandwidth management methods, and data collection through direct observation at Masterpiece Family Karaoke Tebet during peak times. The PCQ implementation involves configuring MikroTik devices to distribute bandwidth fairly among users. Network performance is evaluated based on connection speed, network stability, and perceived service quality by comparing data before and after PCQ implementation. The evaluation results show that implementing the PCQ method on MikroTik devices significantly improves network performance. Connection speed increases, network stability is maintained, and perceived service quality improves. Thus, PCQ proves to be an effective solution for addressing bandwidth management issues at Masterpiece Family Karaoke Tebet.